Development of ADPribosyl Ubiquitin Analogues to Study Enzymes Involved in Legionella Infection. Issue 7 (23rd December 2020) - Kim, Robbert Q.; Misra, Mohit; Gonzalez, Alexis; Tomašković, Ines; Shin, Donghyuk; Schindelin, Hermann; Filippov, Dmitri V.; Ovaa, Huib; Đikić, Ivan; van der Heden van Noort, Gerbrand J.
Abstract: Legionnaires' disease is caused by infection with the intracellularly replicating Gram‐negative bacterium Legionella pneumophila . This pathogen uses an unconventional way of ubiquitinating host proteins by generating a phosphoribosyl linkage between substrate proteins and ubiquitin by making use of an ADPribosylated ubiquitin (Ub ADPr ) intermediate. The family of SidE effector enzymes that catalyze this reaction is counteracted by Legionella hydrolases, which are called Dups. This unusual ubiquitination process is important for Legionella proliferation and understanding these processes on a molecular level might prove invaluable in finding new treatments. Herein, a modular approach is used for the synthesis of triazole‐linked Ub ADPr, and analogues thereof, and their affinity towards the hydrolase DupA is determined and hydrolysis rates are compared to natively linked Ub ADPr . The inhibitory effects of modified Ub on the canonical eukaryotic E1‐enzyme Uba1 are investigated and rationalized in the context of a high‐resolution crystal structure reported herein. Finally, it is shown that synthetic Ub ADPr analogues can be used to effectively pull‐down overexpressed DupA from cell lysate. Abstract : Modular modifications : Analogues of ADPribosylated ubiquitin, including a nonhydrolyzable methylenebisphosphonate version, are constructed and subsequently applied to investigate (de‐)ubiquitinating enzymes involved in Legionella infection. These probes are used in the study of the bacterial effector DupA and the human ubiquitin activating E1 enzyme.